THE EFFECTIVENESS OF DEVELOPING VIDEOS ON VERTEBRATES AND INVERTEBRATES AS A MEANS OF ENHANCING STUDENT LEARNING OUTCOMES - Fadli, Fery; Mahadi, Imam; Wulandari, Sri (Bio-Lectura : Jurnal Pendidikan Biologi, 2025)
Education has a very important role, without education the young generation today will not be able to compete in the international world. Video is a media development that presents audio and visuals containing concepts, principles, mechanisms, theories of knowledge applications to help students' understanding towards learning materials so that the use of learning media supported by technology can improve skills and learning outcomes of students. This study was conducted at MTs Jabalnur Kandis. Biology subjects in the even semester start from May 20, 2023 until completion. This study shows that the average value of student learning outcomes before treatment for the experimental class was 56.7 in the medium category and the control class was 55.1 in the low category. After the provision of learning videos, the experimental class increased the average learning interest of the experimental class to 81.9 in the high category and the control class to 62.8. The n-Gain in the experimental class was 0.58 in the medium category, while the control class n-Gain obtained was 0.17 in the low category.